Higher Mobility Scores in Patients with Cystic Fibrosis Are Associated with Better Lung Function - Thobani, Aneesha; Alvarez, Jessica A.; Blair, Shaina; Jackson, Kaila; Gottlieb, Eric R.; Walker, Seth; Tangpricha, Vin (Pulmonary Medicine, 2015)
Objective. The purpose of this study was to determine whether mobility and physical activity were associated with lung function in adults with cystic fibrosis (CF). Design. This was a prospective cohort observational study in an urban, academic, specialized care center. Participants were ambulatory, nonhospitalized adults with CF. Main Outcome Measures. Mobility was assessed monthly by the Life-Space Assessment (LSA) questionnaire and quarterly by pedometer. Lung function was assessed by spirometry. Results. Twenty-seven subjects participated. Subjects recorded mean pedometer steps of 20,213 ± 11,331 over three days and FEV1% predicted of 77.48% ± 22.60% over one year. The LSA score at enrollment was correlated with initial pedometer steps (r=0.42 and P=0.03), and mean LSA score over one year was correlated with mean number of steps (r=0.51 and P=0.007). LSA mobility and pedometer scores were correlated with FEV1% predicted at enrollment and throughout the study. Conclusions. Mobility and physical activity measured by LSA questionnaire and pedometer are positively associated with lung function in adults with CF. This study confirms the importance of mobility and physical activity and supports the utility of a simple office-based questionnaire as a measure of mobility in adults with CF.